Integration of Islam in the Adat Basandi Syarak, Syarak Basandi Kitabullah in Minangkabau Society: Integrasi Agama Islam dalam Adat Basandi Syarak, Syarak Basandi Kitabullah di Masyarakat Minangkabau - Mariana, Mela; Sibawaihi; Nur Anna, Dian (Indonesian Journal of Islamic History and Culture, 2024)
Islam has undergone a long process of regeneration in Minangkabau, the integration between customs and Islam in Minangkabau is reflected in their philosophy of life, "adat basandi syarak, syarak basandi kitabullah." This philosophy shows that Minangkabau customs are based on Islamic law, and Islamic law is based on the Qur'an. Traditional values and norms as well as the Islamic religion serve as the basis and guideline for people's lives, ensuring that religious traditions and beliefs support each other. This study uses a literature review method. By collecting, evaluating, and synthesizing scientific literature relevant to the topic discussed. Through this research, it is hoped that it can be explored more deeply how the integration of Islam in the tradition of basandi syarak, syarak basandi kitabullah in the Minangkabau community, as well as its impact on their social, cultural, and religious life. The results of the study show that the integration of Islam in the Basandi Syarak Custom, Syarak Basandi Kitabullah in the Minangkabau community combines Islamic values with local customs and traditions, reflecting the close harmony between the two. Ian G. Barbour's integrative approach provides a relevant framework, assisting communities in facing the challenges of globalization and modernity preserving their cultural heritage while strengthening social harmony. The social, cultural, and religious implications of ABS-SBK integration underscore the importance of this strategy as a foundation for strengthening social identity and maintaining cultural diversity and social sustainability in Minangkabau.